The Incentive Effects of the Taxation if Income from Capital in the Italian Corporate Sector - Silvia Giannini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1987)
This research is part of a broader study on fiscal an financial investment incentives. This paper investigates the potential distotions of investment and saving decisions induced by the taxation of income from capital and by investment incentives in the Italian economy.
Keywords: 330